Association of sedentary time and carotid atherosclerotic plaques in patients with type 2 diabetes. Issue 1 (5th January 2022) - Ke, Jing; Li, Kun; Ke, Tingyu; Zhong, Xu; Zheng, Qidong; Wang, Yufan; Li, Li; Dai, Yuancheng; Dong, Qijuan; Ji, Bangqun; Xu, Fengmei; Shi, Juan; et al.
Abstract: Background: Atherosclerosis is a common complication in patients with type 2 diabetes (T2DM). Multiple factors are involved in the development and progress of atherosclerosis. We evaluated the association of weekly sedentary time (WST) with carotid plaque formation. Methods: After data cleaning, a total of 26 664 participants with T2DM from 10 National Metabolic Management Centers (MMCs) from June 2017 to April 2021 were enrolled. Self‐reported lifestyle data including WST, sleeping time, smoking and drinking information, carotid artery ultrasound, and biochemical parameters were obtained. The independent association of carotid plaue with sedentary and other lifestyle behaviors was evaluated using multivariable logistic regression models, and odds ratio (OR) with 95% confidence interval (CI) were reported. Moreover, stratified analysis was conducted to demonstrate the influence of confounding factors. Results: The mean (SD) age of the participants was 54.0 (11.6) years, and the median (interquartile range) WST was 35.0 (21.0, 42.0) h. Comparing with participants in the first tertile of WST, those in the second or third tertile of WST were younger and with a shorter duration of diabetes. There were positive associations between longer sedentary time and odds of artery plaque after adjustment, with corresponding ORs in the second and third tertile were 1.40 (95% CI: 1.31–1.50) and 1.67 (95% CI: 1.56–1.79), respectively. However, the effect of WST on plaque in patients aged 18–40 years old had no statistical significance; the p value in the third tertile was 0.163. Conclusions: In summary, higher WST appears to be associated with higher prevalence of carotid plaque in patients with T2DM, especially in aged populations. Abstract : Highlights This is a multicenter study to evaluate the association of sedentary time with carotid plaque formation. Increased weekly sedentary time appears to be associated with increased carotid plaque formation in patients with T2DM. Age was a confounding factor in this study. 摘要: 背景: 动脉粥样硬化是2型糖尿病患者的常见并发症。动脉粥样硬化的发生发展涉及多种因素。我们评估了每周久坐时间(WST)与颈动脉斑块形成的关系。 方法: 数据清理后, 纳入2017年6月至2021年4月10个国家代谢管理中心(MMC)的26664例2型糖尿病患者。自报生活方式资料包括WST, 睡眠时间, 吸烟和饮酒情况, 颈动脉超声和生化指标。用多变量Logistic回归模型评估久坐与其他生活方式行为之间的独立关联, 并报告95%可信区间(CI)的优势比(OR)。此外, 还对混杂因素进行了分层分析, 论证了混杂因素的影响。 结果: 受试者的平均年龄为54.0(11.6)岁, WST的中位数(四分位数范围)为35.0(21.0, 42.0)小时。与WST前3分位数的受试者相比, WST第二或第三3分位数的受试者年龄更小, 糖尿病病程更短。调整后久坐时间与动脉斑块形成的OR值呈正相关, 调整后2, 3分位数的OR值分别为1.40(95%CI:1.31~1.50)和1.67(95%CI:1.56~1.79)。而WST对18~40岁患者斑块的影响无统计学意义, 第三3分位数P值为0.163。 结论: 高WST似乎与T2 DM患者颈动脉斑块的高患病率有关, 尤其是在老年人群中。